PENDIDIKAN TINGGI ISLAM DI INDONESIA: KONTINUITAS, KONFLIK, DAN ARAH MASA DEPAN (STUDI ATAS PEMIKIRAN RONALD A. LUKENS-BULL) - Agus Hidayatullah; Kosasih; B. Syafuri; Apud (Cakrawala Pedagogik, 2025)
The transformation of Islamic higher education in Indonesia, particularly the transition from IAIN to UIN, is not merely an administrative change, but a complex cultural and intellectual project. Ronald A. Lukens-Bull sees this phenomenon as an effort to build a unique “Islamic Modernity,” in which religion and science are not dichotomously separated. This study aims to analyze Ronald A. Lukens-Bull's thoughts on the evolution of Islamic higher education in Indonesia, focusing on three main elements: continuity, conflict of interests, and the future vision of Islamic education. This study uses a qualitative approach with a library research method. The primary data sources are Lukens-Bull's key works, such as A Peaceful Jihad: Negotiating Identity and Modernity in Muslim Java, as well as his journal articles related to the development of Islamic universities in Indonesia. This study found three crucial points in Lukens-Bull's thinking. Continuity, because Islamic higher education continues to maintain the roots of the pesantren tradition as a moral and intellectual identity. Lukens-Bull calls this “Peaceful Jihad,” where modernization is carried out without abandoning the essence of religiosity. Conflict, due to the emergence of tensions between the demands of global academic standardization (Western) and the preservation of traditional Islamic values. Conflict also occurs at the epistemological level in efforts to integrate religious and general knowledge. Future Direction, because Lukens-Bull projects Indonesian Islamic higher education as a model for the global Muslim world in managing diversity and democracy through a “hybrid” curriculum that balances professional skills with moral-religious character. Lukens-Bull's thinking emphasizes that Islamic higher education in Indonesia is at the forefront of redefining the relationship between Islam and modernity. The future of this institution depends on its ability to manage internal and external conflicts while remaining faithful to its mission of inclusive community service.